Weaknesses and shortcomings of rubberwood as a product - Lew W H; Chew L T (In: Proceedings of the 2nd Rubberwood Seminar, 19-20 November 1985, Forest Research Institute of Malaysia, Kuala Lumpur, Malaysia, pp.30-36., 1985)
While the increase in export volume and value of rubberwood sawntimber have been very encouraging, it must be recognised that rubberwood, as a product, still faces certain shortcomings which must be overcome in order that the rubberwood processing industry can be further consolidated. The need for a quality control system for rubberwood is discussed and an outline of the MTIB quality control system is given.
Keywords: Rubberwood